Oil and Gas Industry Of Ukraine: Regarding the Necessity of Assessment of the Present State and Need of Human Resources - Андибур, А. П. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
In comparison with practices of provision of qualified staff for the oil and gas industry in the USA, the article identifies the corresponding problems in the oil and gas industry of Ukraine. A result of the comparison is list of problems that need to be solved by using the potencial of higher educational institutions of Ukraine. The article also determines the main methods and tasks of science and practice of preparation, development and effective usage of human resources in Ukrainian oil and gas companies.